2018
DOI: 10.1007/s11259-018-9725-1
|View full text |Cite
|
Sign up to set email alerts
|

The effect of ammonia on canine polymorphonuclear cells

Abstract: Hyperammonaemia is a common complication of liver disease in dogs. High concentrations of ammonia can be detrimental to dogs with liver disease for several reasons, notably by causing hepatic encephalopathy (HE) which describes the wide range of neurological abnormalities ranging from altered behaviour to seizures that are well recognised complications in dogs with hepatic disorders. In human patients with liver disease, hyperammonaemia has also been linked to the development of other systemic complications su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…It has been shown that hyperammonemia induces neutrophil swelling, further impairing their phagocytic activity (56)(57). Increased spontaneous oxidative burst was also observed in canine polymorphonuclear cells incubated with ammonia (58). A previous study also demonstrated the inhibitory effect of ammonia on neutrophil chemotaxis (59).…”
Section: Ammonia In Extrahepatic Complications Associated With Cirrhosismentioning
confidence: 88%
“…It has been shown that hyperammonemia induces neutrophil swelling, further impairing their phagocytic activity (56)(57). Increased spontaneous oxidative burst was also observed in canine polymorphonuclear cells incubated with ammonia (58). A previous study also demonstrated the inhibitory effect of ammonia on neutrophil chemotaxis (59).…”
Section: Ammonia In Extrahepatic Complications Associated With Cirrhosismentioning
confidence: 88%
“…The oxidative burst, whereby the neutrophils undergo massive oxygen consumption from the plasma which is then enzymatically converted to reactive oxygen species (ROS) that are targeted against pathogens. In both humans36 and dogs,37 it has been shown that the metabolic imbalances often seen in dogs with hepatic dysfunction can cause spontaneous oxidative bursts in the absence of appropriate stimuli. These ROS are instead released inappropriately with damage to bystander tissues such as endothelium, which can propagate the liver disease 38.…”
Section: Discussionmentioning
confidence: 99%
“…Research into the hepatotoxicity of ammonia is still emerging, but in vitro and animal studies have demonstrated that elevated ammonia may worsen fibrosis by activation of hepatic stellate cells, induce oxidative stress, and promote apoptosis (18,19). Elevated ammonia levels can also disrupt immune cell function (20)(21)(22) and deplete important branched-chain amino acids in skeletal muscles (23).…”
Section: Potential Benefits Of Serum Ammonia Testing ("The Good")mentioning
confidence: 99%